Disease Burden of Dysmenorrhea: Impact on Life Course Potential - MacGregor B; Allaire C; Bedaiwy MA; Yong PJ; Bougie O (International Journal of Women's Health, 2023)
Brittany MacGregor,1 Catherine Allaire,1 Mohamed A Bedaiwy,1 Paul J Yong,1,* Olga Bougie2,* 1Department of Obstetrics and Gynaecology, University of British Columbia, BC Women’s Centre for Pelvic Pain and Endometriosis, Vancouver, Canada; 2Department of Obstetrics and Gynaecology, Queen’s University, Kingston, Canada*These authors contributed equally to this workCorrespondence: Olga Bougie, 76 Stuart Street, Victory 4, Department of Obstetrics & Gynecology, Queen’s University, Kingston, Ontario, Canada, K7L 2V7, Email Ob17@queensu.ca Paul J Yong, Department of Obstetrics & Gynecology, University of British Columbia, FRCSC, F2 – 4500 Oak Street, Vancouver, British Columbia, V6H3N1, Canada, Email Paul.Yong@vch.caAbstract: Dysmenorrhea is the most common gynecologic condition among the female population and has a significant impact on life course potential. It has a widespread impact on a female’s mental and physical well-being, with longstanding impairments on quality of life, personal relationships, and education and career attainment. Furthermore, untreated dysmenorrhea can lead to hyperalgesic priming, which predisposes to chronic pelvic pain. Primary dysmenorrhea is pain in the lower abdomen that occurs before or during menses and in the absence of pelvic pathology. One possible mechanism is endometrial inflammation and increased prostaglandin release, resulting in painful uterine contractions. Dysmenorrhea may also occur secondary to pelvic pathology, such as endometriosis, adenomyosis or due to cyclic exacerbation of non-gynecologic pain conditions. A thorough patient evaluation is essential to differentiate between potential causes and guide management. Treatment must be tailored to individual patient symptoms. Pharmacologic management with non-steroidal anti-inflammatory medications and/or combined hormonal contraceptives is most common. Heat therapy, exercise, vitamins and dietary supplements have limited evidence and can be offered for patients seeking non-pharmacologic adjunctive or alternative options. Greater awareness for both health-care providers and patients allows for early intervention to reduce impact on quality of life and life course potential.Keywords: primary dysmenorrhea, adolescents, chronic pain, health trajectory, women’s health